PROTECTIVE AND DOSE-DEPENDENT EFFECTS OF Cucumis melo SEED OIL ON TESTICULAR FUNCTION AND OXIDATIVE STRESS IN TRICARBALLYLIC ACID – INDUCED TOXICITY IN MALE WISTAR RATS - Enyioma-Alozie, Swesme (FUDMA Journal of Sciences, 2025)
Cucumis melo seed oil (CMSO), rich in polyunsaturated fatty acids, tocopherols, and phenolic antioxidants, has demonstrated antioxidant and anti-inflammatory potential. This study evaluated the dose-dependent protective effects of CMSO on Tricarballylic acid (TCA)-induced testicular oxidative stress and functional impairment in male Wistar rats. Twenty-five male Wistar rats were randomly assigned into five groups (n = 5) and treated orally for 21 days: Control (normal saline), TCA only (200 mg/kg), and TCA (200 mg/kg) co-administered with CMSO at 100, 200, and 300 mg/kg. Body weight, oxidative stress markers (SOD, MDA), reproductive hormones (FSH, testosterone), sperm parameters, and testicular histology were assessed. TCA significantly decreased SOD activity (10.42±1.61 U/mg; p<0.05) and increased MDA (1.25±0.25 nmol/mg) compared to controls (18.02±3.00; 0.80±0.24). Co-administration of CMSO improved SOD activity in a dose-dependent pattern, with the highest level observed at 300 mg/kg (14.77±2.73; p<0.05). Testosterone suppression by TCA (3.22±0.05 ng/mL) was ameliorated by CMSO, especially at 200 mg/kg (4.02±0.45 ng/mL; p< 0.05). FSH levels showed mild dose-related increase. Sperm motility decreased markedly with TCA (35.26±13.35%) but improved only at 300 mg/kg CMSO (45.63±13.75%; p<0.05). Histology revealed focal degeneration, including tubular disorganization and germ-cell loss at medium and high CMSO doses. CMSO exerted dose-dependent biochemical protection against TCA-induced oxidative and hormonal disruptions, with the 300 mg/kg dose showing the greatest antioxidant effect. However, the persistence of histological alterations at higher doses suggests that biochemical improvements do not fully translate to structural recovery, highlighting the need for dose optimization and longer-duration studies to clarify therapeutic potential.